PELAKSANAAN KEGIATAN NEED ASSESMENT BIMBINGAN DAN KONSELING - Tyas, Fildayana Ayuning; Noor, Marzuki; Wibowo, Satrio Budi (Counseling Milenial (CM), 2023)
This research focuses on implementing needs assessments at SMA Negeri 4 Metro. The aim of the research is to determine the Need Assessment activities carried out by Guidance and Counseling teachers, the instruments used by Guidance and Counseling teachers in carrying out Need Assessments and the results of Need Assessments carried out by Guidance and Counseling teachers at SMA Negeri 4 Metro. This research uses qualitative research methods which produce data in the form of information or information regarding the implementation of needs assessments at SMA Negeri 4 Metro. The data sources in this research were 3 Guidance and Counseling teachers. Data collection uses interview, documentation and observation methods to determine the implementation of the assessment, the tools used in the assessment, and the results of the assessment. The results of this research show that the needs assessment carried out at SMA Negeri 4 Metro was carried out offline and online. The assessment is carried out by following assessment procedures starting from identifying problems, testing feasibility, collaborating with parties who can provide data, and analyzing needs. The assessment instruments used by guidance and counseling teachers are in the form of questionnaires and AUM-U format 2. In AUM there are 50 statement items that are filled in by students regarding problems or potential that can be developed by guidance and counseling teachers. The assessment results resulting from the process of analyzing student needs are mapping of service programs that are in accordance with AUM-U.